Pencegahan Kenakalan Remaja melalui Kolaborasi Antara Peran Pendidikan dan Orang Tua - Risqomah, Risqomah; Muslimah, Hanifah; Mudrik, Ahmad; Safitri, Refki; Salsabilla, Zachroha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Juvenile delinquency is a social phenomenon that includes various deviant behaviors carried out by adolescents, such as brawls, theft, drug use, and other violations of social norms. This study aims to identify the causes, impacts, and prevention efforts for juvenile delinquency. Factors that influence juvenile delinquency include internal aspects, such as low self-control and unstable emotions, as well as external aspects, such as peer influence, ineffective parenting patterns, and an unsupportive social environment. The impact of juvenile delinquency involves physical, emotional, and social losses for both the adolescents themselves and the wider community. Effective prevention efforts involve a holistic approach, namely cooperation between families, schools, communities, and the government. Moral education, strengthening the role of the family, social supervision, and providing positive activities for adolescents are strategic steps that can be implemented. In addition, policies are needed that support adolescent development, such as rehabilitation programs and skills training. This study concludes that handling juvenile delinquency requires synergy from various parties to create an environment that supports the development of adolescents into responsible individuals who contribute positively to society.